2013
DOI: 10.1631/jzus.b1200308
|View full text |Cite
|
Sign up to set email alerts
|

Gorham-Stout syndrome in mainland China: a case series of 67 patients and review of the literature

Abstract: Abstract:Objective: Gorham-Stout syndrome (GSS) is a rare disorder of uncertain etiology and unpredictable prognosis. This study aims to present a comprehensive understanding of this rare entity. Methods: A literature search in PubMed and three Chinese databases was performed to screen histologically proven GSS cases among Chinese residents in the mainland. We analyzed the patients' clinical characteristics, the value of different treatment modalities and their influence on the clinical outcome. Results: Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 41 publications
1
55
0
6
Order By: Relevance
“…As a general rule, the persons that suffer from the disease are younger than 40-year-old [16] , while an epidemiologic correlation with race, gender and geography does not seem to exist [9,[17][18][19] . However, some authors noticed a clear "predilection" of the disease in males [20] . Gorham-Stout syndrome is met in a large spectrum of bones, but the majority of case reports refer to the maxillofacial region and the upper extremity [16] .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…As a general rule, the persons that suffer from the disease are younger than 40-year-old [16] , while an epidemiologic correlation with race, gender and geography does not seem to exist [9,[17][18][19] . However, some authors noticed a clear "predilection" of the disease in males [20] . Gorham-Stout syndrome is met in a large spectrum of bones, but the majority of case reports refer to the maxillofacial region and the upper extremity [16] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Gorham-Stout syndrome is met in a large spectrum of bones, but the majority of case reports refer to the maxillofacial region and the upper extremity [16] . Nevertheless, Hu et al [20] recently reported a case series, in which the femur was the predominant affected bone.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Además de las lesiones osteolíticas, concomitantemente, se puede presentar linfangiomatosis, que causa quilotórax, quiloperitoneo o quiloascitis y lesiones quísticas en órganos viscerales, especialmente en el bazo. 7 Los criterios diagnósticos son los siguientes: a) biopsia positiva; b) ausencia de atipia celular; c) mínima o nula respuesta osteoblástica y ausencia de calcificación distrófica; d) evidencia de resorción ósea progresiva; e) lesiones no expansivas y no ulcerativas; f) ausencia de afectación visceral; g) patrón osetolítico radiográfico; h) sin causa hereditaria, metabólica, inmunológica o infecciosa. 7 El tratamiento no es curativo e incluye la radioterapia, medicación antiosteoclástica e interferón alfa-2b.…”
unclassified
“…7 Los criterios diagnósticos son los siguientes: a) biopsia positiva; b) ausencia de atipia celular; c) mínima o nula respuesta osteoblástica y ausencia de calcificación distrófica; d) evidencia de resorción ósea progresiva; e) lesiones no expansivas y no ulcerativas; f) ausencia de afectación visceral; g) patrón osetolítico radiográfico; h) sin causa hereditaria, metabólica, inmunológica o infecciosa. 7 El tratamiento no es curativo e incluye la radioterapia, medicación antiosteoclástica e interferón alfa-2b. La radioterapia es la terapia más efectiva al reducir la progresión de la enfermedad en un 77-80% de los casos.…”
unclassified